Deferring Angioplasty and Stenting based on Natural Progression in Severe Middle Cerebral Artery Stenosis: An Observation of Two Cases - Vita Kusuma Rahmawati; Achmad Firdaus Sani; Dedy Kurniawan; Muh. Wildan Yahya; Faishol Hamdani (Journal of Neurointervention and Stroke, 2025)
Highlight: MCA stenosis may remodel spontaneously or progress to complete occlusion Serial imaging observing progression spots high-risk cases, guiding intervention ABSTRACT Introduction: Severe middle cerebral artery (MCA) stenosis, as one of the intracranial atherosclerotic diseases, is a major cause of ischemic stroke. The role and optimal timing of interventions, such as angioplasty and stenting, remain subjects of debate, particularly due to the variable natural disease progression. While some cases improve spontaneously, others progress to total occlusion, necessitating comprehensive evaluation of individualized treatment approaches. Cases: This case series presents two patients with severe MCA stenosis, each of whom followed a distinct clinical courses. The first patient had 88% stenosis in the M1 segment of the right MCA (NIHSS 3, mRS 2), which spontaneously improved to 57% within days (NIHSS 2, mRS 2), with enhanced distal flow, leading to the decision to defer angioplasty and stenting. In contrast, the second patient initially had severe left MCA stenosis (NIHSS 10, mRS 4), which progressed to total occlusion within three months (NIHSS 10, mRS 4), also resulting in deferred intervention. Serial cerebral digital subtraction angiography (DSA) facilitated the observation of vascular evolution and collateral circulation, guiding decisions about intervention. Conclusion: The clinical outcomes of MCA stenosis range widely, from spontaneous resolution to progressive occlusion. Close serial imaging observation of collateral circulation and natural progression is essential for guiding decisions about angioplasty and stenting.